Risk Factors and Incidence of Feline Lower Urinary Tract Disease (FLUTD) in Sahabat Satwa Genteng Animal Clinic - Plumeriastuti, Hani; Novitasari, Seline Putri; Arimbi, Arimbi; Yunita, Maya Nurwartanti; Hamid, Iwan Sahrial; Wibawati, Prima Ayu (Universitas Airlangga, 2023)
The purpose of this study was to determine the risk factors and incidence of Feline Lower Urinary Tract Disease (FLUTD) at the Sahabat Satwa Genteng clinic. A total of 36 samples were evaluated according to research procedures with diagnosis, data collection, urine sampling, dipstick and sediment examination methods, and Chi-square data analysis. The results showed that there was a association between gender, history of castration, and diet on the risk of FLUTD. Meanwhile, there was no association between age and the risk of FLUTD. Clinical signs that often occur in FLUTD disease initiate from stranguria, hematuria, dysuria, periuria, and polykisuria. The results of the dipstick examination founded that 86,1% of cats affected by FLUTD had a normal pH and 13,9% had an alkaline pH. The results of the specific gravity (SG) of cats with FLUTD have values below normal while the protein levels found in all cats suffering from FLUTD have values above normal. Stranguria was found in 69,4% of cats with FLUTD. Leukocytes were also found in all the urine of cats suffering from FLUTD. The most common results of sediment examination were struvite, calcium oxalate, and cystine crystals.